Contemporary Strategies for Managing and Controlling Viral Outbreaks: An Overview: Contemporary Strategies for Managing and Controlling Viral Outbreaks - Mohammad Ejaz,; Muhammad Ali Syed,; Rani Faryal,; Sheryar Jamil, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Viruses are notorious for causing a significant array of infectious diseases, rendering them a prominent contributor to global morbidity and mortality rates. Throughout history, various regions have experienced outbreaks, epidemics, and pandemics, resulting in significant mortality rates. The Influenza virus gave rise to highly fatal outbreaks that disseminated on a global scale, subsequently resulting in a pandemic during the initial decades of the 20th century. This catastrophic event led to >75 million fatalities, accompanied by a substantial incidence of illnesses. In addition to the development of efficacious treatments for viral diseases, it is imperative to establish and implement various preventive measures to mitigate the transmission of diseases within both local and global populations. Furthermore, it is critical to implement proven conventional and contemporary strategies for managing viral infections, alongside bolstered surveillance systems. Viruses employ diverse modes of transmission, encompassing respiratory, oral-fecal, blood-borne, and vector-borne pathways. Consequently, effective measures to mitigate viral dissemination must be tailored to address each distinct route of transmission. This review discusses the existing strategies employed to mitigate the transmission and containment of viral outbreaks, as well as the dissemination of the disease within a sizable population, intending to reduce their detrimental and fatal impacts on a community.